Whole-wheat flour particle size influences dough properties, bread structure and in vitro starch digestibility. Issue 4 (15th April 2020) - Lin, Suyun; Gao, Jing; Jin, Xiaoxuan; Wang, Yong; Dong, Zhizhong; Ying, Jian; Zhou, Weibiao
Abstract : Whole-wheat flour (WWF) particle size is critical to dough properties, bread quality, and in vitro starch digestibility of bread. Abstract : Whole-wheat flour (WWF) is increasingly popular because of the health benefits of whole grains. This study investigated the effect of WWF particle size on dough properties, bread quality and in vitro starch digestibility. WWF was made from intact whole grain directly. Three WWF particle sizes were examined, including coarse, medium and fine with a mean size of 1315, 450 and 199 μm, respectively. The dough made from WWF of a larger particle size exhibited lower extensibility and stability, and subsequently the bread had a more compact structure ( i.e. lower open porosity and thicker cell thickness), smaller specific volume and harder texture, which were regarded as poor quality attributes. On the other hand, the bread made from the fine WWF exhibited a higher amount of released glucose than those made from the coarse and medium WWFs. Moreover, the particle size of bread bolus showed no significant effect on in vitro starch digestion. The whole study demonstrated that the particle size of WWF plays a critical role in determining both bread quality and digestibility.